On the existence of Alfvén waves in the terrestrial foreshock - J. P. Eastwood; A. Balogh; E. A. Lucek; C. Mazelle; I. Dandouras (Annales Geophysicae, 2003)
The terrestrial foreshock is characterised by the existence of large amplitude ultra low frequency waves. The majority of such waves are observed to be left-handed in the spacecraft frame, but are in fact intrinsically right-handed and have been identified as fast-magnetosonic waves. More rarely observed are waves that are right-handed in the spacecraft frame. Cluster four spacecraft observations of such waves are presented and analysed using multi-spacecraft techniques; in particular the k-filtering/wave telescope technique is used. The waves are found to be left-handed and propagating sunwards in the plasma rest frame, and are, therefore, identified as Alfvénic. The convection of the waves anti-sunward in the solar wind flow causes the observed polarisation to be reversed. Generation mechanisms are discussed. Key words. Interplanetary physics (MHD waves and turbulence; planetary bow shocks) – Space plasma physics (wave particle interactions)